An effective method for hydrogen production in a single-chamber microbial electrolysis by negative pressure control. (13th September 2018) - Feng, Huajun; Huang, Lijie; Wang, Meizhen; Xu, Yingfeng; Shen, Dongsheng; Li, Na; Chen, Ting; Guo, Kun
Abstract: In this study, we construct a scalable tubular single-chamber microbial electrolysis cell that using negative pressure (40.52 kPa) to enhance the hydrogen production. The impact of negative pressure on current production, hydrogen recovery, and microbial community of microbial electrolysis cells are investigated. Negative pressure could effectively enhance the hydrogen recovery and inhibit the growth of methanogens. Consequently, the microbial electrolysis cell operated under negative pressure achieves a maximum hydrogen production rate of 7.72 ± 0.06 L L −1 d −1, which is more than four times higher that of reactor running under normal pressure (1.51 ± 0.41 L L −1 d −1 ). Energy quantification shows that the electrical energy recovery under negative pressure is 146.98%, which is much higher than 95.00% under normal pressure. Therefore, negative pressure control is as effective for increasing hydrogen production and energy recovery in the scalable MEC, and has a great practical application prospect. However, negative pressure cannot knick out methanogens. Once negative pressure is removed, methanogens will quickly take over and after that applying negative pressure again can only partly inhibit methane production. Highlights: Negative pressure inhibits methanogenesis for 30 days in single chamber MECs. Negative pressure enhances the hydrogen recovery by 13 times. Negative pressure improves single chamber MEC energy recovery by 1.5 times. Negative pressure enables a hydrogen production rate of 7.72 L L −1 d −1 .